Seasonal Outflow of Ice Shelf Water Across the Front of the Filchner Ice Shelf, Weddell Sea, Antarctica - E. Darelius; J. B. Sallée (Geophysical Research Letters)
Abstract The ice shelf water (ISW) found in the Filchner Trough, located in the southern Weddell Sea, Antarctica, is climatically important; it descends into the deep Weddell Sea contributing to bottom water formation, and it blocks warm off‐shelf waters from accessing the Filchner ice shelf cavity. Yet the circulation of ISW within the Filchner Trough and the processes determining its exchange across the ice shelf front are to a large degree unknown. Here mooring records from the ice shelf front are presented, the longest of which is 4 years long. They show that the coldest (Θ =− 2.3∘C) ISW, which originates from the Ronne Trough in the west, exits the cavity across the western part of the ice shelf front during late austral summer and early autumn. The supercooled ISW escaping the cavity flows northward with a velocity of about 0.03 m/s. During the rest of the year, there is no outflow at the western site: the current is directed eastward, parallel to the ice shelf front, and the temperatures at the mooring site are slightly higher (Θ =− 2.0∘C). The eastern records show a more persistent outflow of ISW.